Identification and Validation of EMT-Related lncRNA Prognostic Signature for Colorectal Cancer - Li, Danfeng; Lin, Xiaosheng; Chen, Binlie; Ma, Zhiyan; Zeng, Yongming; Wang, Huaiming (Frontiers in Genetics, 2021)
Background: This study aimed to explore the biological functions and prognostic role of Epithelial–mesenchymal transition (EMT)-related lncRNAs in colorectal cancer (CRC). Methods: The Cancer Genome Atlas (TCGA) database were applied to retrieve gene expression data and clinical information. An EMT-related lncRNA risk signature was constructed relying on the comprehensive analysis of the EMT-related lncRNA expression data and clinical information. Then, an individualized prognostic prediction model based on the nomogram was developed and the predictive accuracy and discriminative ability of the nomogram were determined by receiver operating characteristic (ROC) curve and calibration curve. Finally, a series of analyses, such as functional analysis and unsupervised cluster analysis, were conducted to explore the influence of independent lncRNAs on CRC. Results: A total of 581 patients were enrolled and an eleven-EMT-related lncRNA risk signature was identified relying on the comprehensive analysis of the EMT-related lncRNA expression data and clinical information in the training cohort. Then, risk scores were calculated to divide patients into high and low risk groups, and the Kaplan-Meier curve analysis showed that low-risk patients tended to have a better overall survival (OS). Multivariate Cox regression analysis indicated that the EMT-related lncRNA signature significantly associated with prognosis. The results were subsequently confirmed in the validation dataset. Then, we constructed and validated a predictive nomogram for OS base on the clinical factors and risk signature. Functional characterization confirmed this signature could predict immune-related phenotype and was associated with immune cell infiltration (i.e., macrophages M0, M1, Tregs, CD4 memory resting cells, and neutrophils), tumor mutation burden (TMB). Conclusions: Our study highlighted the value of the 11-EMT-lncRNA signature as a predictor of prognosis and immunotherapeutic response in CRC.